THE APPLICATION OF EDIBLE COATING BASED ON NATRIUM ALGINATE ENRICH WITH LEMONGRASS OIL (Cymbopogon citratus) ON TILAPIA FISH FILLET (Oreochromis niloticus) FOR INHIBITED MICROBIOLOGICAL AND OXIDATIVE DAMAGE DURING COLD STORAGE - Sekar Maharani Retnaningtyas; Lia Umi Khasanah; Ardhea Mustika Sari (JITIPARI, 2021)
Tilapia fish fillet have a high protein contain (18,70g/100g) however it can be easily decay. The aim of this study was to know the characteristic of lemongrass oil, characterisric of edible film with the addition of lemongrass oil and quality of tilapia fish fillet coated with edible film-natrium alginate enriched lemongrass oil on cold storage. Edible coating based on alginat added with lemongrass oil and applied on fishery products, tilapia fish fillet. The studies used Complete Random Design 2 factor, lemongrass oil concentration and storage time. Analyzed used one way ANOVA and continued with Duncan’s Multiple Range Test (a:0.05) and paired t-test (a:0.05). The analysis showed that yield of lemongrass oil was 0.27%; specific gravity was 0.85476 g/ml; viscosity was 0.021 N.m/s2 and have 17 active compound. Inhibitory zone of lemongrass oil between 6.417 mm – 20.333 mm. Thickness of edible film added with lemongrass oil between 0.063mm-0.104mm; tensile strength value 1.974 MPa-2.563 MPa and WVTR 4.454 g/jam.m2-5.165 g/h.m2. The result of application edible coating enriched with lemongrass oil on fillet showed the TBA and TPC value were significantly increased during however it didn’t affect significantly to the TVB and pH value. Edible coating enriched lemongrass oil 1.5% able to maintain microbiological quality until day 3 and oxidative quality until day 12